2004
DOI: 10.1152/ajpheart.00580.2003
|View full text |Cite
|
Sign up to set email alerts
|

Strain softening is not present during axial extensions of rat intact right ventricular trabeculae in the presence or absence of 2,3-butanedione monoxime

Abstract: . Strain softening is not present during axial extensions of rat intact right ventricular trabeculae in the presence or absence of 2,3-butanedione monoxime. Am J Physiol Heart Circ Physiol 286: H708-H715, 2004; 10.1152/ajpheart.00580.2003.-Recent studies of passive myocardial mechanics have shown that strain softening behavior is present during both inflation of isolated whole rat hearts and shearing of tissue blocks taken from the left ventricular free wall in pigs. Strain softening is typically manifested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…However, no such effect has been reported in high (12) or low (14,27) Ca 2ϩ in skinned cardiac preparations. Furthermore, even if a BDM-induced increase in the passive tension-length relation had been observed in intact cardiac trabeculae [which is unlikely, because Kirton et al (21) found no increase], this would more likely have caused an increase of stiffness at all frequencies [as observed during the formation of rigor cross bridges (20)] than the frequency dependence shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, no such effect has been reported in high (12) or low (14,27) Ca 2ϩ in skinned cardiac preparations. Furthermore, even if a BDM-induced increase in the passive tension-length relation had been observed in intact cardiac trabeculae [which is unlikely, because Kirton et al (21) found no increase], this would more likely have caused an increase of stiffness at all frequencies [as observed during the formation of rigor cross bridges (20)] than the frequency dependence shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 95%
“…However, when right ventricular trabeculae from rat are subjected to such experimental conditions, spontaneous, asynchronized "waves" of contractile movement, commonly called "writhing," are reported (7,13,21,41). In trabeculae that were deemed to be viable, raising the temperature to 25°C significantly reduced the degree of writhing (7,21 ] i (and, hence, the degree of cross-bridge cycling and resting tension) is higher at lower temperatures in nominally quiescent cardiac muscle tissue. Such phenomena have been reported, without elaboration, during dynamic stiffness measurements of intact, quiescent kitten papillary muscles, in which increased temperature resulted in decreased dynamic stiffness (34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations